Comparative efficacy of intravenous injection of bone marrow mesenchymal stem cells in rats with model of Parkinson-like syndrome - Vladimir Pyatikop; Mohammad Ahmad Msallam Jr; Elena Shchegelskaya; Igor Kutovoy; Galina Gubina-Vakulik; Tetyana Gorbach (Ukrainian Neurosurgical Journal, 2014)
The purpose: to study efficacy of intravenous injection of human and rat bone marrow mesenchymal stem cells (BMMSC) in rats with Parkinson-like syndrome (PS), modeled by chemical degradation of substantia nigra (SN).Materials and methods. Animals were divided into 5 groups: I — intact (n=7); II — PS, bilateral injection of 6-OHDA in SN (n=15); III — PS, intravenous injection of human BMMSC (0.5x106 cells per 1 rat) (n=9); IV — PS, intravenous injection of rat BMMSC (1x106) (n=9); V — PS, intravenous injection of rat BMMSC (2x106) (n=9). Cells were injected 2 weeks after PS modelling. Efficacy of intravenous injection of stem cells was estimated by recovery of movements, changes of dopamine level in blood and brain frontal lobe of the rats and morphological changes of SN.Results. Intravenous injection of human BMMSC at PS helps to restore movement for 14–15 days, normalize DA level in the blood and tissue of frontal lobe of the rats on the 10th day and increase the number of neurons in damaged SN area.Intravenous injection of rats BMMSC (in doze 1x106) was inefficient, partial restoration of movement and DA level normalization in the blood and in tissue of frontal lobe was observed only to 20–21 day. Intravenous injection of rat BMMSC (in doze 2x106) at PS helps to restore movement to 9–10 day, normalize DA level in the blood and tissue of frontal lobe on 10th day, active neurons in SA are observed.Conclusions. Intravenous injections of rat and human BMMSC are effective for treatment of PS symptoms in rats, the results depend on the amount of injected cells.